The Effect of Slope Chamfer on Hydroponic NFT (Nutrient Film Technique) System For Cultivitation Of Japan Spinach (Spinacia Oleracea L.) - Elvina, Wica; Utami, Risnita Tri (University of Prof. Dr. Hazairin, SH, 2024)
One of the technological developments in the field of agriculture is agricultural cultivation technology with a hydroponic system. The category of hydroponic systems that are currently widely used is hydroponics with the NFT (Nutrient Film Technique) system. NFT is a hydroponic cultivation system by putting the roots of plants in a thin layer of water where the plants get nutrients from the nutrient solution that flows through the gutters, the flow of nutrient on NFT hydroponic circulated continuously so that the plant's nutritional needs can be fulfilled. NFT hydroponic vegetables is suitable to be cultivated for leafy vegetables, like a Japanese spinach plant (Spinacia Oleracea L.). The purpose of these research was to test the design of NFT Hydroponic with slope 3%. In the testing performance of hydroponic NFT consist of three parameters. These parameters include the testing of irrigation efficiency, pH values ​​and Electrical Conductivity (EC) solution and the uniformity of crop productivity. Data obtained from this study were analyzed based on its design to determine the effect of each parameter on plant growth. The highest irrigation efficiency value on day 11 was 92.00% and the lowest on day 24 was 89.42%, the value indicates that there is water loss in the water slope caused by several factors. The highest electrical conductivity (EC) uniformity value reached 92.10% and the lowest was 86.95%, this percentage indicates the high nutrients contained in the water flow in the reservoir. The highest pH solution uniformity value reached 99.51% and the lowest was 91.18%. These three factors indicate that the analysis of the three values ​​is quite uniform in each gutter. Based on the results of NFT hydroponic growth, it looks quite varied so it can be concluded that it is less uniform. The smallest weight of the Japanese spinach plant produced was 13 grams while the largest was 70 grams. The uneven weight of the plant can be influenced by less than optimal environmental conditions and the selection of nutrients that are not right for Japanese spinach plants.